(untitled) (Archives of Criminology, 2008)
The purpose of the text is to present the difference between the practical work of the family court in dealing with minors and the ideas referring to such work. The author begins by presenting the principles of juvenile proceedings and stresses the importance of the principle of the good of the juvenile. The text then characterises the measures imposed on minors on the basis of fundamental data of court statistics, the structure of which has not changed significantly over the years, according to the author. Witold Klaus lists the following measures: probation supervision, obliging the juvenile to behave in a certain way, or sending them to a juvenile detention centre. The publication is based on the author’s own research, which examined the structure of family court decisions against minors under the age of 13. Referring to the conclusions of the analysis, Klaus emphasises first of all the higher percentage of discontinued or pending cases, the less frequent probation supervision, and decisions to place minors in institutions, which are common for this category of decisions. The author also outlines the problem of a sense of guilt lacking in the parents of minors, who blame the deeds of their children on others during the proceedings and try to defend them under any circumstances. Klaus brings attention to charging the parents with the costs of the proceedings, which, according to him, can be a quasi-measure to encourage a sense of responsibility in the guardians’ for their children’s behaviour. The text also discusses court rulings in follow-up studies aiming to trace the influence of court cases on the further criminal career of juveniles and to analyse the judges’ adjudication. To conclude the paper, the author comments on the effectiveness of measures applied to juveniles by family courts and analyses them based on the objectives of the proceedings. Klaus once again highlights the gap between the observable practice of dealing with juveniles and its underlying assumptions. He suggests necessary changes in the juvenile justice system involving, for instance, building a cooperation network made up of various institutions and introducing prevention programmes based on the findings of criminological research.